PENDIDKAN NILAI MORAL PADA ANAK USIA DINI DI ERA PANDEMI COVID 19 - Supriyanto Supriyanto; Masrukhi Masrukhi; Eny Winaryati (Universitas Sriwijaya, 2021)
AbstractThis study was used to explore the inculcation of moral values in students during the COVID-19 pandemic. The purpose of this study was to examine how the education of values in early childhood in the Covid 19 pandemic era. The method used was qualitative. The results showed: (1) Education Moral values in the Covid 19 pandemic era carried out at TK Al Hidayah IV are: (a) Education of religious values, (b) Education of moral values, (c) Education of social values. Conclusion: (1) The education of moral values in students is carried out using the method of assigning students to students, (2) The method of moral value education is adjusted to the conditions of the students (3) To facilitate the learning process at home the teacher coordinates with the parents of the students. Recommendations: (1) Schools need support from the government in the learning process in the Covid pandemic era, (2) The learning process in the Covid pandemic era requires collaboration between teachers and parents of students, (3) In the distance learning process, teachers, students and people need to be aware of health protocols.Keywords: Early childhood, Values, Morals, Education, Social. AbstrakStudi ini digunakan untuk menggali penanaman nilai moral pada siswa pada pandemi covid 19. Tujuan dari penelitian ini adalah untuk mengkaji bagaimana Pendidkan nilai pada anak usia dini pada era pandemic Covid 19. Metode yang digunakan kualitatif. Hasil penelitian menunjukkan: Pendidikan nilai moral pada era pandemic covid 19 yang dilaksanakan di TK Al Hidayah IV adalah adalah nilai agama dan moral, fisik motorik, kognitif, bahasa, sosial dan seni. Kesimpulan: Konsep, kendala dan dampak pendidikan nilai moral pada anak usia dini pada era pandemi covid 19 mencakup koginif, emosional dan budaya siswa. Rekomendasi: (1) Sekolahan membutuhkan dukungan dari pemerintah di dalam prososes pembelajaran di era pandemic covid, (2) Proses pembelajaran di era pandemic covid membutuhkan kerjasama antara guru dan orang tua siswa, (3) Di Dalam proses pembelajaran jarak jauh, guru, siswa dan orang perlu meperhatikan protokol kesehatan.Kata Kunci: Anak usia dini, Nilai, Moral, Pendidikan, Sosial,